2014
DOI: 10.1074/jbc.m114.595512
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Macromolecular Complex Formation of Lysophosphatidic Acid Receptor 2 (LPA2) Mediates Gradient Sensing in Fibroblasts

Abstract: Background: Chemotaxis is a fundamental process in many physiological and pathological events. Results: An LPA gradient induces a spatiotemporally restricted decrease in the mobility of LPA 2 indicative of its cytoplasmic anchorage to NHERF2, the cytoskeleton and PLC␤, which causes a gradient of localized Ca 2ϩ puffs. Conclusion: Asymmetrical macromolecular complex formation by LPA 2 mediates gradient sensing. Significance: Our finding provides a new mechanistic basis to help understand chemotactic gradient se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Interestingly, it has been observed that β-arrestin is not required for PMA-induced LPA 1 receptor internalization [ 64 ], which further emphasizes the differences between LPA-mediated processes and those induced by pharmacological activation of PKC. Agonist-triggered internalization of LPA 2 receptors has also been studied [ 60 , 65 ]. In one of these works clear agonist-induced receptor internalization was observed [ 60 ] whereas in the other, internalization was slow and very limited in magnitude [ 65 ]; marked differences in the experimental conditions (i. e., cell types, conditions for LPA exposure and in the detection of membrane receptors) might explain the disparate results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, it has been observed that β-arrestin is not required for PMA-induced LPA 1 receptor internalization [ 64 ], which further emphasizes the differences between LPA-mediated processes and those induced by pharmacological activation of PKC. Agonist-triggered internalization of LPA 2 receptors has also been studied [ 60 , 65 ]. In one of these works clear agonist-induced receptor internalization was observed [ 60 ] whereas in the other, internalization was slow and very limited in magnitude [ 65 ]; marked differences in the experimental conditions (i. e., cell types, conditions for LPA exposure and in the detection of membrane receptors) might explain the disparate results.…”
Section: Discussionmentioning
confidence: 99%
“…Agonist-triggered internalization of LPA 2 receptors has also been studied [ 60 , 65 ]. In one of these works clear agonist-induced receptor internalization was observed [ 60 ] whereas in the other, internalization was slow and very limited in magnitude [ 65 ]; marked differences in the experimental conditions (i. e., cell types, conditions for LPA exposure and in the detection of membrane receptors) might explain the disparate results. Interestingly, LPA 2 receptors are key elements in the formation of the macromolecular complexes that mediate LPA gradient sensing in fibroblasts [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4+ T cells in mice lacking LPA2 ( Lpar2 −/− ) display a severe defect in cell motility during the early homing process at the lymph nodes (Knowlden et al, 2014 ). LPA2 is also required for gradient sensing during the chemotaxis of fibroblasts (Ren et al, 2014 ). In an in vivo model of collective cell migration, LPA2 induces cell-cell dissociation and promotes a partial epithelial-mesenchymal transition (EMT) in Xenopus neural crest (NC) cells by down-regulating cell-cell adhesions (Kuriyama et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAGI-3 had a negative regulatory effect on LPA 2 mediated cell function [17]. Studies have shown that spatial organization of PDZ motif-mediated LPA 2 receptor macromolecular complex assembly mediates LPA gradient sensing in fibroblasts [18]. LPA mediates anti-apoptosis of cells through LPA 2 receptor, and the damage repair effect of LPA 2 receptor on DNA can protect cells from radiation to some extent [19].…”
Section: Lpar2mentioning
confidence: 99%